2013
DOI: 10.1002/ajmg.a.36153
|View full text |Cite
|
Sign up to set email alerts
|

De novo 13q deletions in two patients with mild anorectal malformations as part of VATER/VACTERL and VATER/VACTERL‐like association and analysis of EFNB2 in patients with anorectal malformations

Abstract: Anorectal malformations (ARMs) comprise a broad spectrum of conditions ranging from mild anal anomalies to complex cloacal malformations. In 40-50% of cases, ARM occurs within the context of defined genetic syndromes or complex multiple congenital anomalies, such as VATER/VACTERL (vertebral defects [V], ARMs [A], cardiac defects [C], tracheoesophageal fistula with or without esophageal atresia [TE], renal malformations [R], and limb defects [L]) association. Here, we report the identification of deletions at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Human embryological studies have demonstrated that the primitive urogenital sinus and anorectal canal originate from the primitive cloaca, and there are number of molecular events that govern the developmental processes underlying cloacal septation, closure of the perineum and scrotum, urethral tubularization and penoscrotal positioning (2628). The results obtained from patient 1 in the present study, together with those obtained from patients with genitourinary/anorectal anomalies in 13q deletion syndrome from previous studies (3,4,68,11,1418), have identified two critical regions, 13q33.3-qter and 13q22.1–31.3. In recent years, the non-morbid online Mendelian Inheritance in Man (OMIM) gene, ephrin B2 ( EFNB2 ) located in 13q33.3, has been recognized as a strong candidate gene for hypospadias or anorectal anomalies in 13q deletion syndrome in a number of studies (4,79,18).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Human embryological studies have demonstrated that the primitive urogenital sinus and anorectal canal originate from the primitive cloaca, and there are number of molecular events that govern the developmental processes underlying cloacal septation, closure of the perineum and scrotum, urethral tubularization and penoscrotal positioning (2628). The results obtained from patient 1 in the present study, together with those obtained from patients with genitourinary/anorectal anomalies in 13q deletion syndrome from previous studies (3,4,68,11,1418), have identified two critical regions, 13q33.3-qter and 13q22.1–31.3. In recent years, the non-morbid online Mendelian Inheritance in Man (OMIM) gene, ephrin B2 ( EFNB2 ) located in 13q33.3, has been recognized as a strong candidate gene for hypospadias or anorectal anomalies in 13q deletion syndrome in a number of studies (4,79,18).…”
Section: Discussionsupporting
confidence: 81%
“…1 and Table II, and a summary of the regions on chromosome 13 identified in the present and previous studies (3,4,68,10,11,1422) are reviewed in Fig. 2.…”
Section: Case Reportmentioning
confidence: 96%
See 1 more Smart Citation
“…These include: (i) deletions of 5q11.2 [25], 6q [26], 7q35-qter [27], distal 13q [28,29], 19p13.3 [30], and 20q13.33 [31]; (ii) duplications on 1q41, 2q37.3, and 8q24.3 [32], 9q [33] and at 22q11.21 [34]; (iii) deletion at Yq with duplication at Yp [35], and deletion of 9p24.3-p24.1 with duplication of 18q12.3-q23 [36]; (iv) supernumerary der(22) syndrome [37]; (v) mosaicism for supernumerary ring chromosome 12 [38] or 18 [39]; and (vi) partial monosomy 16p13.3pter/partial trisomy 16q22qter [40]. The smallest of these microaberrations was identified in the study by Hilger et al [32], describing a de novo microduplication at 2q37.3 with an estimated size of 25kb.…”
Section: Chromosomal (Micro-)aberrations In Patients With Vater/vactementioning
confidence: 99%
“…The etiology of the VACTERL association is not still fully understood, although HOXD13 , ZIC3 , PTEN , FANCB , FOXF1 , and TRAP1 mutations have been reported as possible contributors to the VACTERL association or the VACTERL-like association as described previously [29]. Several microduplications and microdeletions are also reportedly associated with the VACTERL association [10, 11]. However, these findings have had sparsely be replicated.…”
Section: Introductionmentioning
confidence: 98%